‘But it’s really about …’ : Norwegian Media Coverage of the Qur’an Burnings in Sweden and Norway in April 2022 - Toft, Audun (Temenos - Nordic Journal for the Study of Religion, 2024)
This article examines the Norwegian media coverage of and public debate about a series of anti-Muslim demonstrations in which Qur’ans were burned in Sweden and Norway over the Easter of 2022. Conceptualizing Qur’an burnings and the ensuing riots in Sweden and Norway as a media event, the article explores how different actors manage, negotiate, and use the mediated attention constituting such an event. The empirical material consists of all articles published by ten selected Norwegian newspapers between 14 and 30 April 2022, as well as interviews with seven journalists from these newspapers. A key point the article makes is that news journalists are mindful of how they cover and frame such an event. They take steps to ensure that their coverage accords with professional journalistic standards. The analysis shows, however, that the media coverage is complex and multi-layered, and that news journalists’ managing strategies only influence a small part of the total coverage and debate. A media event is by its nature discursive, and the article discusses how the event’s ‘real meaning’ is contested as various actors within and outside the media reframe it to fit already established discourses.